Ethics in the Workplace - Goree, Keith
Examine ethical situations in the workplace through the lens of ethical decision-making models with ETHICS IN THE WORKPLACE. Drawing from news headlines and cases based on well-known people, the text combines theory, real-world examples of ethical situations workers face, role plays, and class discussion, and provides ethical decision-making models and a constant focus on self-reflection and moral reasoning